Ensaios sobre economia da educação: escola pública, impactos e consequências - Carvalho, Thiago Costa (2021)
This thesis is composed of two independent essays in the field of economics of education that have public school as the object of study. The first essay aims to evaluate the effect of public school in the different ranges of student results in Enem, seeking to capture the differences in performance from the analysis by quantile. To this end, a model based on quantile regression is used to capture the difference in conditioning factors along the distribution of results and the semi-parametric model of sample selection based on regression by extreme quantiles is applied to overcome the endogeneity problem. The results point to a significant difference in educational opportunities to the disadvantage of public school students. The second essay seeks to identify the consequences of the implementation of the PNE proposal for democratic management in public elementary schools from the 5th to 9th grade on educational quality. To this end, a longitudinal data analysis is employed, considering the Ideb score per school. The estimation considered robust and clustered standard errors to overcome the heteroscedasticity problem. The results indicate the importance of training managers and teachers to improve the quality of public schools.